The Benefits, Factors, and Barriers Faced in the Implementation of Digital National Early Warning Score in Hospitals: A Scoping Review - Fricilia Noya; Yanny Trisyani; Etika Emaliyawati (Universitas STRADA Indonesia, 2025)
Digital National Early Warning Score (NEWS) is a system designed to detect early clinical deterioration in patients by monitoring vital parameters using digital technology. The implementation of Digital NEWS in hospitals is increasingly gaining attention because of its ability to improve patient safety, efficiency in clinical decision-making, and reduce the workload of health workers. However, although many benefits have been identified, implementing Digital NEWS is open to various challenges and obstacles. This study aimed to explore the benefits, factors, and obstacles faced in implementing digital NEWS in Hospitals. This scoping review used the Arksey and O'Malley framework following the PRISMA for Scoping Review. Literature searches used three main databases: EbscoHost: Medline Ultimate, Pubmed, and Scopus, and also one search engine, Google Scholar. Ten relevant articles were analyzed in this study. Implementation of digital NEWS can improve early detection of deteriorating patient conditions, reduce medical response time, and improve communication between health teams. However, the success of its implementation is influenced by several factors, such as the availability of technological infrastructure, adequate training, and technological literacy among health staff. The main challenges include lack of resources, alarm fatigue, and cultural resistance to technological change. This review concludes that implementing digital NEWS has many benefits, but health workers still face many challenges and barriers. A comprehensive approach is needed to optimize the benefits of digital NEWS implementation, including investment in infrastructure, training, and managerial support.